Factors influencing the capital structure of sharia construction and building companies - Ghazali Syamni, Said Musnadi,; Mitra Prasetyo5Jumadil Saputra3, umt.edu.my Irfan4, (Opción, 2019)
This study aims to amine the effect of tangibility, non-debt tax shields, firm size, profitability, and receivables to the capital structure by using panel regression based on the Common Effect model, fixed effect model and random effect model. The results of this study showed that there was a negative influence of tangibility and firm size on the capital structure. Research implication concludes that investors should be more careful choosing a company, to invest their capital by looking at reliability, non-debt tax shields, firm size, profitability, and receivables to improve the expected capital structure.